27.2 COMPREHENSIVE CARDIOVASCULAR RISK REDUCTION TRIAL IN PERSONS WITH SERIOUS MENTAL ILLNESS - Daumit, Gail (Schizophr Bull, 2019)
BACKGROUND: Persons with SSD and other SMI die 10–20 years earlier than those without. Much premature death in this population is attributable to cardiovascular disease (CVD) with CVD-related mortality rates twice those of the overall population. Accordingly, this vulnerable group has a high burden of modifiable CRF including smoking, obesity, hypertension, diabetes, and dyslipidemia. Interventions need to be adapted for persons with SSD and other SMI who often have substantial barriers related to cognitive impairment and psychiatric symptoms. Our objective was to determine the effectiveness of an 18-month comprehensive CVD risk reduction intervention in adults with SSD and other SMI. METHODS: We recruited adults with SSD or another SMI and with at least one CRF from community mental health programs and randomly assigned them to an intervention or a control group. Participants in the intervention group received health behavior coaching and care coordination/care management to improve CRF. The primary outcome is the change in estimated CVD risk from the global Framingham Risk Score between baseline and 18 months. Individual CRF comprise secondary outcomes. RESULTS: The trial enrolled 269 participants. Mean age is 48.8 (SD 11.9) years, 48% are male, 50% are White, and 46% are African American. At baseline, 90 percent are overweight, approximately half smoke tobacco, half have hypertension, over a third have diabetes mellitus, and approximately two-thirds have dyslipidemia. The trial is ongoing. The 18-month outcome results will be presented. CONCLUSIONS: Unless effective interventions that effect CVD health outcomes are implemented, populations with SSD and other SMI will continue to lag far behind public health CVD goals. This intervention incorporates care coordination and care management concepts with intensive health behavior change coaching to address all CRF in persons with SSD and other SMI in community mental health settings. If successful, the intervention could be adopted broadly and significantly improve the physical health of this vulnerable population.